PENINGKATAN POTENSI CEKER BROILER HASIL SAMPING DARI TEMPAT PEMOTONGAN AYAM (TPA) MENJADI GELATIN DENGAN MENGGUNAKAN METODE EKSTRAKSI TERKOMBINASI - Miwada, I Nyoman Sumerta; Simpen, I.N. (Bumi Lestari; Vol 9 No 1 (2009), 2009)
This research was proposed to increased the potency of shanks, esspeciality their skin by hidrolising the collagen (by extrating with solvent) into gelatine products. This research was run on a Completely Randomized Design (CRD). The experiment was run in factorial designs of 2 x 3. Factor I was solven type chloroform-ethanol and heksana-etanol, Factor II was a combination of ratio of 1:1, 1:3, and 3:1. The variable in this research were pH, viscosity, rendement, protein, and fat of gelatine contents. Result of the research indicated that the pH value of gelatine was between 8.21-8.52. The solvent of chloroform-ethanol gave the best result (P<0.05) on the ratio of 1:3. Percentage of rendement of gelatine was highest obtained from chloroform-ethanol types compared with that of hexane-ethanol (P<0.05). The interaction combinations of chloroform-ethanol on the ratio of 1:1 would result in the rendement percentage to be higher than others (P<0.05). Otherwise, the solvent of hexane-ethanol might bring impact to the viscocity of gelatine (P<0.05) compared to chloroform-ethanol. The interaction combination of hexane-ethanol ratio gave the best result (P<0.05) with highest level of viscosity on the ratio of 3:1 and lower on 1:3. The content of gelatine protein was highest (P<0.05) for the combination of hexane-ethanol compared to that of chloroform-ethanol. The solvent of chloroform-ethanol types could degrade more component of gelatine fat (P<0.05) compared to that of hexane-ethanol. It could be concluded that the research that the content of gelatine protein from extraction by hexane-ethanol on the combination ratio of 3:1 brought the highest quality compared to others.
Keywords: shanks; by product; protein collagen; extraction; gelatine